The Interference Cancellation and Doubly Selective Channel Estimation in FBMC-based OFDM Systems - Jangoni Srikanth (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Filter Bank Multicarrier (FBMC) transmission technique is universally applicable for upcoming wireless communication standard 5G technology in design of physical layer protocol. It is compared to the existing 4G technology such as Orthogonal Frequency Division Multiplexing (OFDM). In OFDM, there are drawbacks like high power consumption, low energy efficiency, high error rate and a smaller number of users. To overcome these problems, main requirement of 5G technology is to increase the data rate about 1000 times. Thus, FBMC is preferable physical layer prototype. FBMC uses one filter for a group of sub carriers. Filter bank multicarrier uses a different modulation technique known as multicarrier modulation. Multicarrier modulation is a form of signal waveform that uses multiple carriers normally closely spaced in a block to carry the information. These blocks of carriers are positioned in a bank known as a filter bank. The performance of each Filter bank multicarrier is considered by Throughput, Data rate, Bit error rate (BER), Mean square error (MSE), Peak to average power ratio (PAPR). The result of this study shows that Filter bank multicarrier depicts a satisfactory improvement in performance.